2014
DOI: 10.7162/s1809-48722010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Trauma Patients Maxillofacial Surgery at the Hospital Geral de Blumenau SC From 2004 to 2009

Abstract: Summary Introduction:?Accidents involving the face have increased incidence in the last four decades. The medical literature refers to the increase in motor vehicle collisions and urban violence as the major causes of injuries, especially in young individuals. Objective:?Raise the epidemiological profile of 222 patients with facial fractures at the Hospital Santo Antonio from 2004 to 2009. Method:?Case study with retrospective analysis of records of patients diagnosed with facial fractures. Several variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
1
1
3
Order By: Relevance
“…In that analysis, the LOS of maxillofacial trauma in-patients in our data was 6 days, which is in keeping with a different Malaysian study that reported a mean LOS of 5.8 days 16 . Our results remain within the range of studies performed worldwide, where the mean LOS was reported to be between 2 days and 10.6 days 4 , 17 - 20 .…”
Section: Discussionsupporting
confidence: 86%
“…In that analysis, the LOS of maxillofacial trauma in-patients in our data was 6 days, which is in keeping with a different Malaysian study that reported a mean LOS of 5.8 days 16 . Our results remain within the range of studies performed worldwide, where the mean LOS was reported to be between 2 days and 10.6 days 4 , 17 - 20 .…”
Section: Discussionsupporting
confidence: 86%
“…The average length of hospital stays (LOS) in present study (18.12 days) was found to be longer than that of 2.5 days reported by Martins Junior et al 37,38 The reason for this difference is that in the present study patients with multiple maxillofacial fractures, associated injuries, and those with associated lower limb fractures had significantly longer hospital stay contributing significantly to the overall mean LOS.…”
Section: Discussioncontrasting
confidence: 55%
“…Sedangkan penelitian yang dilakukan Montovani et all (2006) menemukan penderita fraktur fasial terbanyak pada mahasiswa/siswa. 14 Pada Tabel 4 diperoleh bahwa penderita fraktur fasial terbanyak ditemukan pada penderita yang memiliki alamat di kecamatan Malalayang sebanyak 49 kasus (31,41%). Lebih banyaknya penderita fraktur fasial yang memiliki alamat di kecamatan Malalayang kemungkinan oleh karena letak RSU Prof. Dr. R.D.…”
unclassified
“…Dalam rangkaian lebih dari 200 fraktur fasial yang terlihat di pusat perkotaan, penyerangan dilaporkan terjadi hampir 50%. 14 Pada Tabel 6 diperoleh bahwa lokasi fraktur terbanyak pada penderita fraktur fasial ditemukan pada tulang mandibula sebanyak 70 kasus (39,77%). Hasil ini hampir sama dengan yang dilaporkan oleh Chrcanovic et al (2004) pada studi dari 1326 fraktur fasial pada 911 kasus, bahwa fraktur tulang fasial lebih banyak pada tulang mandibula, diikuti oleh tulang zigoma dan tulang hidung.…”
unclassified
See 1 more Smart Citation